Statue of Stephen the Great in Iaşi (Confluenţe Bibliologice, 2023)
The article reviews essential data on erection of the Statue of Stephen the Great in front of the Palace of Culture in Iași, dedicated to Stephen the Great (1457-1504), the Moldavian ruler, the most legendary figure in the history of Moldova. The idea of raising the ruler's statue belongs to Theodor Balș, deputy of the ruler of Moldavia between July 1856 and February 17, 1857. After many debates, Stephen's statue was entrusted to the French sculptor Emmanuel Frémier (1824-1910). Also, in the article are highlighted, the stages of sculpture, the basic elements of sculpture and the contribution of the outstanding personalities of the cultural and scientific life of those times.
Keywords: Stephen the Great and Saint; historical personality; Romanian history